An Analysis of the Schrodinger Equation Model for the Distribution Rate of Stock Returns - Agus Kartono; Hilda Meiranita Prastika Dewi; Irmansyah Irmansyah (Universitas Andalas, 2023)
Quantum mechanics is a theory that describes the behavior of particles in the microscopic world. If the stock index can be considered an object on a macro scale, then every stock of a stock index is an object on a micro-scale. The stock price can be analogous to being a particle. This study aimed to obtain the density distribution of stock returns. Modeling stock returns distribution using a Schrodinger equation model with the assumption that stock is a particle in the good delta potential function so that stock returns as analogous to particles can be known. The Schrodinger equation can calculate stock returns expressed as an exponential distribution. The stock return density distribution using Schrodinger equation model has a higher kurtosis value than the kurtosis value in the normal distribution. The kurtosis value is the degree of the peak height of a distribution. The stock price data used is the stock price data of PT. United Tractors Tbk. and PT. Unilever Indonesia Tbk. during 2013-2018. This study shows the stock price of PT. Unilever Indonesia Tbk. has a more stable average stock price return with a more negligible risk of loss than the stock price of PT. United Tractors Tbk.